Impulsivity trajectories and gambling in adolescence among urban male youth. (3rd January 2013) - Liu, Weiwei; Lee, Grace P.; Goldweber, Asha; Petras, Hanno; Storr, Carla L.; Ialongo, Nicholas S.; Martins, Silvia S.
Abstract Aim Building on the recent emerging literature on the impulsivity trajectory–gambling association, this study investigated the association between developmental trajectories of teacher‐rated impulsivity in early adolescence (ages 11–15 years) and subsequent gambling and gambling problems (i.e. at‐risk and problem gambling) by age 19. Design Prospective cohort design. Setting Urban communities in Baltimore, Maryland. Participants The sample consists of 310 predominately minority (87%) and low socio‐economic status (SES) (70%) males followed from first grade to late adolescence. Measurements Impulsivity was measured using teacher ratings of classroom behavior. Self‐reported gambling behavior was assessed using the South Oaks Gambling Screen‐Revised for Adolescents (SOGS‐RA). Findings Results from a conventional growth model suggest that the intercept of the impulsivity development (as measured by the repeated assessments of impulsivity across the entire developmental period) was associated significantly with gambling. Results from a general growth mixture model evidenced two distinct trajectories: a high impulsivity trajectory (41% of the sample) and a low impulsivity trajectory (59% of the sample). Despite its non‐significant association with any gambling, heterogeneity in impulsivity development was associated significantly with gambling problems. Specifically, being in the high impulsivity trajectory doubled the odds of meeting criteria for at‐risk or problem gambling [odds ratio (OR) = 2.09, 95% confidence interval (CI): 1.02, 4.27)] and tripled the odds of meeting criteria for problem gambling (OR = 2.84, 95% CI: 1.02, 7.91). Conclusions Development in impulsivity is associated strongly with problem/at‐risk gambling in adolescence among urban male youth. Findings highlight the importance of distinguishing gambling problems from any gambling when evaluating programs aimed at reducing youth gambling problems through reducing impulsivity.